The prophet's pulpit : Islamic preaching in contemporary Egypt - Gaffney, Patrick D., 1947- (Comparative studies on Muslim societies ;, 1994)
Muslim preaching has been central in forming public opinion, building grassroots organizations, and developing leadership cadres for the wider Islamist agenda. Based on in-depth field research in Egypt, Patrick Gaffney focuses on the preacher and the sermon as the single most important medium for propounding the message of Islam.